Cervical Rib a Very Rare Cause of Secondary Raynaud's Phenomenon - Siddiqui, MR; Mahbub, MS; Mostafiz, T (Anwer Khan Modern Medical College Journal, 2014)
Secondary Raynaud's phenomenon (or syndrome) due to thoracic outlet obstruction or syndrome (TOS) from cervical rib is very rare. Cervical rib occurs in only 1% of the general population. It is an uncommon cause for thoracic outlet syndrome (TOS). The clinical manifestations of thoracic outlet syndrome are mainly neurological. Arterial complications are rare and potentially severe. The authors report a case of a 30 year-old woman with left cervical rib that developed embolism in the subclavian artery, due to compression. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21133 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 49-50